Investigation of several critical issues in screen mesh heat pipe manufacturing and operation - Engelhardt, Andreas (2010)
The PhD thesis with the title “Investigation of several critical issues in screen mesh heat pipe manufacturing and operation” presented hereafter describes work carried out in four main areas. Initially the relevant literature is reviewed and presented, followed by the presentation of theoretical work regarding screen mesh heat pipe fill calculations, heat pipe processing and an investigation into the capillary or lifting height for screen mesh heat pipes. Further, the possibility of tailoring screen mesh heat pipes towards certain applications was investigated and it was found that further work is required in this area to allow a conclusive judgement whether a coarser or finer wick at the wall provides a distinguish advantage over two wraps of a medium coarse type. Within this approach a calculation method for the determination of the optimum working fluid fill of a screen mesh heat pipe based on geometrical parameters of the wick was developed and successfully implemented for the production of the later tested samples. The investigation into the effects of bending on the heat pipe performance, both using single phase flow CFD as well as experimentation, was performed using five different geometrical cases, each with five samples. These were tested in order to minimise the effects of sample variation. The test cases investigated contained the deformation angles of 0° (straight), 45°, 90°, 135° and 180°. During all test cases the orientation of the samples was kept constant at 0° to minimise additional influences like the effects of gravity on the reduction of available power handling capability. The test results show in deviation from CFD results that screen mesh heat pipe performance is significantly affected when bends are introduced and the reduction in power handling capability can be up to nearly 50% of a straight heat pipe value. Finally this thesis advances into the field of water heat pipe freeze thaw and the possibility of screen mesh heat pipes with changed shapes to withstand multiple freeze thaw cycles. It was found that correctly engineered screen mesh copper water heat pipes can be used in applications where they are subjected to multiple freeze thaw cycles. The fluid charge for water heat pipes subjected to these conditions needs to be adjusted in such a way, that accumulation of working fluid in certain areas, regardless of orientation or process variation during filling, is avoided.